Evidence for Chemical Vapor Induced 2H to 1T Phase Transition in MoX2 (X = Se, S) Transition Metal Dichalcogenide Films - Adam L. Friedman (Nature Portfolio, 2017)
Abstract Electron-donors can impart charge to the surface of transition metal dichalcogenide (TMD) films while interacting with the film via a weak physisorption bond, making them ideal for vapor and gas sensors. We expose monolayer MoS2 and MoSe2 films to strong electron-donor chemical vapor analytes. After analyzing the resultant behavior and taking into consideration doping effects, we conclude that exposure to strong electron-donors could be a method of inducing the semiconductor-metal 2H-1T TMD phase transition. We find that the conductance response to strong electron donors in both monolayer MoS2 and MoSe2 FET devices ceases after moderate exposure, with final value of the conductance being on order of that expected for the 1T phase. Full device relaxation back to a semiconducting state is accomplished by annealing in vacuum at 400 °C. We also examine chemically exposed TMD films intermittently interrogated with Raman and photoluminescence spectroscopy. We observe the appearance of weak characteristic 1T phase Raman features for MoS2 and we observed a quenching of the photoluminescence of both TMD films that is recoverable with annealing. Considering all of our data together, the effects cannot be described by doping alone. Additionally, our results suggest a mechanism for a new type of passive chemical vapor sensor.